Pengaruh Pengetahuan Keuangan, Sikap Keuangan dan Kontrol Diri terhadap Manajemen Keuangan Pribadi: Studi Kasus Mahasiswa UKI Toraja Fakultas Ekonomi Angkatan 2022 - Fita Marissa; Stefani M. Palimbong; Abedneigo.C.Rambulangi (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2025)
This study aims to analyze the influence of financial knowledge, financial attitudes, and self-control on personal financial management among students of the Management Study Program at the Faculty of Economics, Universitas Kristen Indonesia Toraja, class of 2022. The research uses a quantitative approach, distributing questionnaires to 83 respondents selected through the Slovin formula. The data is analyzed using multiple linear regression, as well as validity, reliability, classical assumption, and hypothesis testing. The results show that financial knowledge has a positive and significant effect on personal financial management, while financial attitudes and self-control do not have a significant partial effect. However, simultaneously, the three independent variables have a significant impact on the students' personal financial management. These findings suggest that students' personal financial management is influenced by a combination of financial understanding, attitudes toward money management, and the ability to control their financial behavior. This indicates the importance of enhancing financial knowledge as a key factor in improving personal financial management among students, while attitudes and self-control need further attention to achieve better financial management.